Demo Abstract: Augmenting Homes with Custom Devices using .NET Gadgeteer and HomeOS - Scott, James; Brush, A.J.; Mahajan, Ratul (Proceedings of BuildSys 2012, 2012)
We describe how two of our recent research technologies, .NET Gadgeteer and HomeOS, complement each other in enabling research using custom devices in home deployments. .NET Gadgeteer enables rapid prototyping of custom devices based on solderless assembly from a wide range of publicly available hardware modules, and uses C# managed software to offer a simple and rapid software prototyping experience. HomeOS provides abstraction layers so that “apps” can be written for homes which leverage devices deployed in the home (e.g. wireless sensors, webcams) using standard APIs so that apps are not dependent on a particular hardware interfaces. In combination, HomeOS and .NET Gadgeteer make it easy to construct custom devices which interact with HomeOS apps – addressing problems such as network association (e.g. WiFi credentials), device discovery and functionality discovery “under the covers”. We showcase an example custom device and application – a plumbing leak sensor and leak notification application.